(untitled) (Contemporary Mathematics, 2024)
Background: One of best ways to repel harmful viruses like corona is using of repulsive force between spinors which are existed within structures of cells and viruses. These spins could be induced within virus and cell structures by external magnetic fields which are emitted from currents of ions within blood cells. Motions of charges and ions within blood vessels produces magnetic fields. These fields force on spinors within cell and virus structures within alveolus and make them parallel. These spinning viruses interact with triplet spins of oxygen molecules within alveolus. According to the Pauli exclusion principle, parallel spinors repel each other and anti parallel spinors attract each other. Thus the triplet state of spinors of oxygen molecules could help cells to repel viruses with the same induced spin states. On the other hand, by using external waves, one can induce virtual viruses with opposite induced spins within alveolus and cancel effects of real viruses. We use of this property in controlling viral diseases. Purpose: Our aim is to 1. propose a mathematical model which use of repulsive force between parallel spinors and attractive force between anti parallel spinors within structures of oxygen molecules; alveolar cells and viruses to control COVID-19 disease. 2. We also introduce a mechanism mathematically to induce virtual viruses with opposite spinor states around real viruses within alveolus. These virtual viruses cancel effects of real viruses and form harmless bubbles. 3. We introduce a quantum mask to use of spinor interactions and repel viruses. Method: In this model, hemoglobin molecules and their irons, take special spins from heart waves, move along vessels and induce them to spinors within the structure of other cells like alveolar ones. These spinors select oxygen triplet molecules with opposite spins and repel parallel spin ones. Also, spinors which form RNAs and proteins of viruses could take parallel or opposite spins of any external magnetic field. These spinning viral structures are attracted by opposite spinors of alveolar cells and repel the oxygen molecules with parallel spins. This causes to a decrease in number of needed oxygen molecules within human’s body. To control these viruses, we build a system which includes: 1. A vessel of water and oxygen molecules which be located near the face and is open. 2. A vessel of viruses which is located far from the face and is closed. 3. A heater-cooler system which connects two vessels. Results: During the respiration, alveolar air molecules go out, collide with vessels, attract oxygen and viral molecules with opposite spins and repel parallel ones. Consequently, viruses which could be attracted by alveolar cells go away from the face and build a mask against any similar spinning virus in another end of system. On the other hand, spinors around the viruses in second and closed vessel which couldn’t be attracted by alveolar cells, form some bubbles. By heating and cooling the system these bubble shapes are induced in open vessel of system, make virtual viruses and bubbles which fly towards the face and alveolus. These virtual viruses attract real viruses and make spin-less bubbles which are harmless and go out of human‘s body. We formulate the model and obtain related currents. Conclusion: By using repulsive forces between triplet oxygen states and spinors within viral structures and induction of virtual viruses with opposite spins around real viruses; harmful effects of these viruses could be cancelled. Because; spinors of viruses are surrounded by anti parallel spinors of oxygen molecules and virtual viruses and harmless bubbles and pairs are formed. We have formulate the mechanism and obtained frequencies of waves which induce virtual viruses within alveolus.